Hiring Under Constraint: How School Administrators Perceive and Respond to Centralized Screening by the District - Jennifer L. Nelson; Marisol Jimenez; Paul Bruno (AERA Open)
Prior research on school reform implementation has demonstrated that school leaders may translate policies into practice in ways that either promote or undermine the policy’s goals. To generate a more in-depth understanding about how principal attitudes toward policies relate to how they implement them, we applied insights from the sociological theory of professional control. We drew on interviews with 30 school administrators who were experiencing the rollout of a more rigorous and centralized screening protocol for teacher applicants in the Los Angeles Unified School District. We found that principals’ perceptions of the policy ranged from positive to very negative, and they also varied in how much discretion they exercised in their own subsequent hiring practices. Perhaps counterintuitively, principals with positive perceptions of the district’s protocols enacted the most assertive strategies to recruit teachers. Our findings advance research and theory on how school leaders’ attitudes about policies influence policy implementation.